Sequentially Irradiated and Annealed Highly Cross-Linked Polyethylene: Linear Vector and Volumetric Wear in Total Hip Arthroplasty at 10 Years - Ethan A. Remily, DO (Elsevier, 2021)
Background: There is a paucity of data on the long-term performance of highly cross-linked polyethylene (HXLPE). Therefore, this study evaluated 10-year 1) functional, 2) radiographic, and 3) surgical outcomes in patients who underwent total hip arthroplasty with sequentially irradiated and annealed HXLPE. Methods: A retrospective, multicenter study was conducted on patients who underwent primary total hip arthroplasty and received HXLPE polymer (n = 151). Two-dimensional radiographic linear and volumetric wear analyses were quantified using the Martell Hip Analysis software, while functional outcomes were assessed by analyzing postoperative Short-Form-12 (SF-12) Physical and Mental Health Surveys and Harris Hip Scores. Radiographic outcomes included yearly linear (mm/y) and volumetric (mm3/y) wear rates. Surgical outcomes included additional operations and survivorship. Results: SF-12 scores were within 1 standard deviation (SD) of the normal population (SF-12 Physical: 47.0; SF-12 Mental: 52.0), while the Harris Hip Scores of 89.5 was borderline between “good” and “excellent.” Total and annual linear wear rates were 0.164 mm (SD: 0.199 mm) and 0.015 mm/y (SD: 0.018 mm/y), respectively. The mean total volumetric wear rate was 141.4 mm3 (SD: 165.0) and 12.6 mm3/y (SD: 14.9 mm3/y) when broken down into a yearly rate. Eleven patients required revisions, resulting in an all-cause polyethylene survivorship of 92.7%, with a polyethylene wear survivorship of 100.0%. Conclusions: Our results demonstrate clinically undetectable linear and volumetric wear rates after 10 years in those who received the unique sequentially irradiated and annealed HXLPE. Furthermore, high rates of survivorship coupled with low all-cause revision rates illustrate the polymers' capability to potentially increase implant longevity.